Evaluasi Sistem Arsip Berbasis Cloud Di RSUD Mataram Kota - Alfareza; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
Hospitals generate a large volume of archives daily, particularly patient medical records, laboratory results, radiology reports, and administrative documents. The increasing volume of these archives poses challenges to conventional storage systems, such as limited physical space, risk of damage, data loss, and slow document retrieval processes. To address these issues, many hospitals are transitioning to cloud computing-based archiving systems. This study aims to evaluate the effectiveness of cloud-based archiving systems at RSUD Kota Mataram in terms of access speed, data security, cost efficiency, and compliance with medical record regulations. The method used is descriptive qualitative with a field study approach. Data were collected through in-depth interviews, direct observation, and documentation studies. The findings are expected to provide insights into the benefits and challenges of implementing cloud archiving systems as a basis for decision-making for hospital management.